Glymphatic system dysfunction in chronic tinnitus patients with sleep disturbance - Du, Yinjuan; Huang, Zhichun; Xu, Jin-Jing; Xue, Yuan; Che, Zigang (Frontiers in Neurology, 2025)
PurposeThe neural mechanisms of sleep disturbance associated with chronic tinnitus remains unknown. To investigate this issue, multimodal magnetic resonance imaging (MRI) was used to detect glymphatic system dysfunctions in chronic tinnitus patients with sleep disturbance.MethodsThis prospective study included 30 tinnitus with sleep disturbance (TSD), 30 tinnitus with no sleep disturbance (TNSD) and 38 age, sex, and education-matched healthy controls (HCs). All the subjects underwent MRI scans of the glymphatic indexes and clinical assessment. Multimodal MRI indices were used as proxies of glymphatic function and the relationships between the glymphatic function and sleep disturbance were further evaluated.ResultsTSD group exhibited significantly higher choroid plexus volume (CPV) and enlarged perivascular spaces (EPVS) values than the HCs group (p < 0.0001). Moreover, the TNSD group revealed significantly lower diffusion tensor image analysis along the perivascular space (DTI-ALPS) values than the HCs group (p = 0.044). In chronic tinnitus patients, the decreased DTI-ALPS index was negatively associated with the Pittsburgh Sleep Quality Index (PSQI) scores (r = −0.428, p = 0.001). In addition, the increased CPV and EPVS values were positively correlated with the PSQI scores (r = 0.374, p = 0.005; r = 0.335, p = 0.013; respectively). Furthermore, reduced ALPS values were negatively associated with the Tinnitus Handicap Questionnaires (THQ) scores (r = −0.378, p = 0.005).ConclusionUsing multimodal MRI approaches, this study provides preliminary evidence for disrupted glymphatic function in chronic tinnitus patients, which may be associated with sleep disturbance. CPV, EPVS, and ALPS could serve as neuroimaging markers and shed new light on neuropathological mechanisms for chronic tinnitus comorbid with sleep disturbance.